Desenvolvimento de um jogo sério para treinamento de amputados de membros superiores - Cavalcante, Reidner Santos (2018)
The development of virtual environments as a support tool in the rehabilitation processes has proved to be valid and important for the users, providing a differentiated and fun way to execute the procedures. The more immersed and motivated the user feels in the virtual environment, there is less chance of him giving up the rehabilitation process and there is more chance of getting better levels of use. The connection of the virtual environment with the application of serious gaming characteristics makes it favorable to create a system that allows the user to evolve in their rehabilitation process, as they enjoy the tasks and challenges proposed. However, the development of an environment like this requires the right choice from the interaction devices to the modeling of the environment and the definition of the tasks and the challenges of the game. In this context, this work proposes the development of a virtual training environment for amputees to minimize their time to adapt to a real prosthesis, using a tether with different sensor to interact with the virtual environment. The training protocols were provided by healthcare professionals and the interaction technology was developed under the supervision of them, seeking to make sure that the satisfactory level of mobility and comfort for the user will be high.